On The Experience of Developed Socialism in the Soviet Union - Lakis, Juozas (Problemos, 1977)
Some theoretical questions of developed socialism are considered in the article in terms of the experience gained in the Soviet .Union. The peculiarities of developed socialism in the Soviet Union were determined by a whole complex of historical, national-political conditions and international conditions under which the country developed. The developed socialism in the USSR is characterized by a powerful material and technical basis. The process of social integration and political consolidation at this stage marks a formation of a new historical community – the Soviet people. The Marxist-Leninist world outlook and collectivism have got firmly rooted in the Soviet society, the importance of spiritual motives in its life and activities has gradually increasing. The Soviet socialist way of life has become an important result of socialist development and an index of maturity of social relations. The experience of the Soviet Union testifies to high organization qualities of the developed socialist society. This society provides an optimum combination (within the limits of possible) of social, collective, and personal interests; it develops evenly and harmoniously.